Validity test of a mobile learning-based circuit training model for football players - Artanayasa, I Wayan; Satyawan, I Made; Adinata Kusuma, Ketut Chandra; Dharma Hita, I Putu Agus (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study aimed to examine the validity of a mobile learning-based circuit training model for football players. A development approach consisting of three main stages: needs analysis, model development, and validation, was employed. The study included 50 students (41 males and 9 females) aged 19–23 years (M = 20 years) enrolled in a football course at the Faculty of Sports and Health, Universitas Pendidikan Ganesha. Data were collected through expert evaluations and participant feedback and analyzed using descriptive statistics. The needs analysis revealed a demand for innovative training models integrating technology to address the limitations of traditional methods, such as monotony and lack of flexibility in evaluation time. The developed model was validated by three experts in sports training, educational technology, and evaluation, achieving an average validity score of 4.74, classified as very valid. Participants reported that the model was user-friendly, effective, and aligned with their training needs. The implementation of this model also demonstrated significant potential in enhancing participant engagement during training sessions. These findings confirm that the proposed model is valid and represents a promising alternative to traditional training methods. Furthermore, the model contributes to the development of technology-based sports training that is flexible and engaging, supporting coaches and players in achieving their training objectives more efficiently.